Developing Supply Chain to Increase Firm Performance: The Role of Supply Chain Agility, Supply Chain Integration and Supply Chain Quality Management - Badawi, Badawi (Universitas Muhammadiyah Tangerang, 2024)
The objective of this study was to analyze the effect of supply chain agility (SCA), supply chain integration (SCI) and supply chain quality management (SCQM) on the performance of online food seller companies. This research is quantitative research with a structural equation model methodology using AMOS. This study uses a population of companies or culinary business people who sell their products online in West Java, Indonesia. From this population, 160 online culinary businesses were selected as samples in this study. This study resulted that SCA, SCI and SCQM can have a positive and significant effect on company performance. Online culinary companies should increase supply chain agility through the development of several aspects within the company, namely demand management, agile distribution, agile manufacturing and agile customization. The results fill the gap in previous research by analyzing the influence of supply chain agility, supply chain integration and supply chain quality management on company performance in the culinary industry. It is hoped that this research can provide input and study the role of the supply chain in improving company performance